2011
DOI: 10.1007/978-1-4614-0106-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Microbes and Community Service Through Manipulation of Innate Immunity

Abstract: The periodontal pathogen Porphyromonas gingivalis undermines major components of innate immunity, such as complement, Toll-like receptors (TLR), and their crosstalk pathways. At least in principle, these subversive activities could promote the adaptive fitness of the entire periodontal biofilm community. In this regard, the virulence factors responsible for complement and TLR exploitation (gingipain enzymes, atypical lipopolysaccharide molecules, and fimbriae) are released as components of readily diffusible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 88 publications
(144 reference statements)
0
40
0
Order By: Relevance
“…The net outcome of periodontal disease extent and severity appears dependent upon the characteristics of the oral microbial ecology. These include colonization/emergence of some opportunistic pathogens that appear to alter the local environment affecting the overall microbiome attributes and burden, and act in concert with host responses that are regulated by genetics and modified by the environment in humans [Kinane and Bartold, 2007; Hajishengallis et al, 2012; Armitage, 2013; Ebersole et al, 2013; Wade, 2013; Kornman and Polverini, 2014; Duran-Pinedo et al, 2014]. Since descendants of each of these matrilines still exist within the population and preliminary data suggests an increased risk of demonstrating periodontitis in living animals within the 065 matriline.…”
Section: Discussionmentioning
confidence: 99%
“…The net outcome of periodontal disease extent and severity appears dependent upon the characteristics of the oral microbial ecology. These include colonization/emergence of some opportunistic pathogens that appear to alter the local environment affecting the overall microbiome attributes and burden, and act in concert with host responses that are regulated by genetics and modified by the environment in humans [Kinane and Bartold, 2007; Hajishengallis et al, 2012; Armitage, 2013; Ebersole et al, 2013; Wade, 2013; Kornman and Polverini, 2014; Duran-Pinedo et al, 2014]. Since descendants of each of these matrilines still exist within the population and preliminary data suggests an increased risk of demonstrating periodontitis in living animals within the 065 matriline.…”
Section: Discussionmentioning
confidence: 99%
“…A recent example of these types of interbacterial processes that appear to occur in pathogenic oral biofilms are based upon the capacity of P. gingivalis to undermines critical components of innate immunity, including altering functional levels of effector molecules, as well as receptors and subsequent intracellular signaling pathways required for effective host responses. These authors suggested that these “subversive activities” of the periodontal pathogen could promote the adaptive fitness of the pathogenic biofilm communities and enable the chronicity of the inflammatory response resulting in the tissue destruction of periodontitis [108]. …”
Section: Models Of Multispecies Biofilm Functionmentioning
confidence: 99%
“…Numerous studies have intended to characterize the host response to infection in periodontal/periapical diseases; providing valuable information on the interactions between the bacterial biofilm and the responding host cells [9][10][11]. With the progress of our knowledge from purely descriptive observations towards more mechanistic findings, we are beginning to get a reasonable glimpse of the whole picture.…”
Section: Introductionmentioning
confidence: 99%